The Effect of Knowledge, Promotion, Religiosity, and Consumer Income on the Decision-Making of Being a Financing Customer at KSPPS BMT Nurul Jannah Gresik - Nely Agustin; Farid Ardyansyah (International Journal of Managemen Analytics (IJMA), 2023)
This research was conducted to determine the effect of knowledge, promotion, religiosity, and consumer income on decision-making to become financing customers at KSPPS BMT Nurul Jannah Gresik. The results of this study indicate that knowledge (X1) has a partially positive and significant influence on customer decisions. This is based on the results of the t-test of knowledge = 3.122, then T count > T table or 3.122 > 1.664, with a significance value of 0.001 < 0.05. This is based on the results of T count Promotion = 1.367, then T count > T table, or 1.367 > 1.664 with a significance value of 0.175 > 0.05. Religiosity (X3) has a positive and partially significant effect on customer decisions, this is based on the results of T count: Religiosity = 2.093, then T count > T table, or 2.093 > 1.664, with a significance value of 0.039 < 0.05. Income (X4) has a positive and partially significant effect on customer decisions, this is based on the results of T count Income = 6,500, then T count > T table or 6,500 > 1.664 with a significance value of 0,000 < 0.05. R square value shows 0.744, or the equivalent of 74.4%